2018
DOI: 10.1186/s12912-018-0292-0
|View full text |Cite
|
Sign up to set email alerts
|

“We’ll check vital signs only till we finish the school”: experiences of student nurses regarding intra-semester clinical placement in Ghana

Abstract: BackgroundClinical practicum is an integral part of nursing education because it provides students with opportunities to perform nursing care and practice specific nursing tasks. In Ghana, little is known about the experiences of baccalaureate student nurses with regard to intra-semester clinical practicum. This study therefore, explored perceptions, challenges, and how the intra-semester clinical practicum affects the learning process of student nurses in a private university in Ghana.MethodsExploratory descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…Also, inadequate supervision and poor interpersonal relationship exists between students' and clinical supervisors and that negatively impact students' learning outcomes. These findings are in line with as some studies findings [2,3,15] have reported a lack of proper supervision.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, inadequate supervision and poor interpersonal relationship exists between students' and clinical supervisors and that negatively impact students' learning outcomes. These findings are in line with as some studies findings [2,3,15] have reported a lack of proper supervision.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, the study findings revealed showed some congruence with other studies internationally Abdulmutalib et al [12], Bäck et al, [13], Mbakaya et al [14] and locally in findings of Adjei et al [15] that students' exposure to clinical practicum have impact on students learning outcome. Positively in our study, majority of the study participants expressed some satisfaction with the clinical exposure.…”
Section: Discussionsupporting
confidence: 82%
“…There are several issues that prevent conducive learning environment to occur. Students explained that they were unable to practice certain skills due to lack of resources, lack of diversity of cases and high number of students in one area 8,11 . Also, the students were left unsupervised during clinical placement and as a result, adverse incidents sometimes occurred which confirmed that it is important for the student to be supervised during clinical placement 12 .…”
Section: Conducive Learning Environmentmentioning
confidence: 99%
“…The student-nurse relationship plays a role in the learning experience for the student nurses, it can either be a positive or negative experience depending on what kind of relationship that the student and nurse had. For a positive and friendly relationship between students and nurses it can increases the students' self-confidence and learning 9 , whereas poor student-nurse relationship had negative impact on the students' skill acquisition on the ward 11 . Even though Jahanpour et al 9 claimed that a positive and friendly student-nurse relationship can facilitate the students' learning, however, in their study, the relationship from the nurses was not respectful in such a way that the nurses did not trust the student's work and they blamed the student if anything happened in the ward.…”
Section: Student-nurse Relationshipmentioning
confidence: 99%
See 1 more Smart Citation